THE INFLUENCE OF RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, CAPITAL EARNING) AND INFLATION ON FINANCIAL DISTRESS (Case Study In The Banking Sector Listed On The IDX In 2018-2022) - Safitri, Marlia Hartati; Ranidiah, Furqonti; Junaidi, Ahmad; Yuniarti, Nensi (Universitas Muhammadiyah Bengkulu, 2025)
This research aims to examine the influence of RGEC (Risk Profile, Good Corporate Governance, Capital, Earning) and Inflation on financial distress (Case Study in the Banking Sector Listed on the Indonesian Stock Exchange in 2018-2022. This is a quantitative study with secondary data. The population in this study consisted of 47 companies using sampling techniques using certain criteria or Purposive Sampling so that a sample of 17 companies with a research period of 5 years was obtained so that the data used amounted to 85. Data collection techniques used documentation. Data analysis techniques using SPSS (Statistical Package For Social Sciences). The research results show that the Risk Profile influences Financial Distress with a significant value of 0,000. Good Corporate Governance influences Financial Distress with a significant value of 0,000. Capital influences Financial Distress with a significant value of 0,000. Earning has no effect on Financial Distress with a significant value of 0.101. Inflation has no effect on Financial Distress with a significant value of 0.281. Risk profile, Good Corporate Governance, Capital, Earning and inflation have a simultaneous impact on Financial Distress with a significant value of 0,000